Fear of COVID-19 and stress in university students: mediating role of cyberchondria and moderating role of creative coping and social supports - Sohail, Marva; Zafar, Nida (Journal of the Pakistan Medical Association, 2022)
Objective: To find the moderating role of social support and creative coping, and the mediating role of cyberchondria in relationship between fear of coronavirus disease-2019 and stress in university students. Method: The correlational study was conducted at the Lahore Garrison University, Lahore, Pakistan, between May and September 2020, and comprised students regardless of gender and age from different public and private universities across Pakistan. Data was collected online using Fear of Coronavirus Disease-2019 Scale, Cyberchondria Severity Scale, Creative Coping Strategies Scale, Social Support Survey, Perceived Stress Scale and Perception of Academic Stress Scale. Data was analysed using SPSS 22. Results: Of the 205 subjects, 83(40.5%) were males and 122(59.5%) were females. The overall mean age was 21.22+/-1.84 years. Fear of coronavirus disease-2019 had significant positive relationship with cyberchondria, and cyberchondria had significant positive relationship with creative coping and academic stress (p<0.05). Social support had significant negative relationship with general stress (p<0.05). There was significant interaction among fear of coronavirus disease-2019, creative coping, social support and cyberchondria in predicting general stress (p<0.05). Fear of coronavirus disease-2019 alone did not predict stress (p>0.05), but it significantly predicted cyberchondria which, in turn, predicted stress (p<0.05). Creative coping and social support significantly moderated the relationship involving fear of coronavirus disease-2019, cyberchondria and general stress (p<0.05). The female subjects utilised more creative coping strategies, received more social support, and had higher levels of general stress compared to the males (p<0.05), while the male subjects had more mistrust on medical professionals (p<0.05). —Continue